Edukasi Ibu Rumah Tangga Cegah Stunting Demi Kesehatan Masa Depan Anak Di Posyandu Kunden - Refa Regita Aulia Diwanti; Rayhan Ristu Pratama; Resti Nur Halizah; Restu Albarani Azis; Sri Budi Raharjo (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Stunting remains a challenge to child health and development in Indonesia. Although the government has implemented various efforts, ranging from specific to sensitive interventions, stunting rates in several regions still show alarming data. A lack of maternal knowledge has been shown to contribute significantly to stunting. Limited information about breastfeeding, proper complementary feeding, infectious disease management, hygiene, and growth monitoring leads many mothers to be inaccurate in caring for their children, especially regarding nutritional needs. Therefore, we use outreach methods to provide knowledge to housewives on how to prevent stunting in toddlers. Recognizing the signs of stunting in children is important for parents. Recent studies have also shown that educational programs at Integrated Health Posts (integrated health post) can increase maternal awareness and change their behavior in feeding and child health care. The low level of understanding among housewives about stunting and its prevention. Many housewives do not yet understand that stunting is not simply a condition of short stature in children but a. chronic nutritional problem that causes impaired brain development, reduced learning ability, decreased productivity, and increased risk of degenerative diseases in adulthood.